Deproteinization stabilises dentin bonding of self-adhesive resin cements after thermocycling - Souza, Lidiane Costa de (2016)
This study examined the effect of deproteinization on the microtensile dentin bond strength (µTBS) and nanoleakage (NL) of conventional and self-adhesive resin cements after 24 h or after 20,000 thermocycles. Occlusal dentin of thirty-two human molars were distributed into four groups according to the type of cement used: conventional or self-adhesive; and the strategy of luting: RelyX ARC/Single Bond 2 (RAc) following the manufacturer׳s instructions (control), RelyX ARC/Single Bond 2 (RAd) applied after dentin deproteinization; RelyX U200 (RUc) following the manufacturer´s instructions (control); RelyX U200 (RUd) applied after dentin deproteinization. The specimens were cut into non-trimmed dentin–composite sticks and the half sticks of each group were subdivided into two subgroups: 24 h water storage and after 20,000 thermal cycles, before microtensile bond test. For NL, 5 bonded sticks from each subgroup were prepared and analyzed under SEM. Three-way ANOVA showed that the dentin deproteinization increased the µTBS of both cements, although the RAd group showed a decrease on the µTBS after thermocycling. Chi-square test showed significant loss of specimens by premature failure for the groups after thermocycling, except for the RUd group. The dentin deproteinization improved the initial µTBS and decreases the NL of both cements tested, but, after thermocycling, this technique is only effective for RelyX U200.